Circulating CD45+EpCAM+ cells as a diagnostic marker for early-stage primary lung cancer - Sun, Zhen; Li, Peng; Wu, Zhaojun; Li, Bin; Li, Wenjing; Zhao, Mingming; Zhou, Xiaobin; Wang, Zeyao; Yu, Zhongjie; Liu, Wenna; Zhu, Wenshu; Wang, Haibo; et al. (Frontiers in Medical Technology, 2022)
Lung cancer is a highly prevalent type of cancer, accounting for 11.6% of all cancer incidences. Early detection and treatment can significantly improve the survival rate and quality of life of patients; however, there is no accurate, effective, and easy-to-use test for early lung cancer screening. In this study, flow cytometry was used to detect the presence of CD45+EpCAM+ cells in tumor tissues and peripheral blood mononuclear cells (PBMCs) in patients with lung cancer. Moreover, the proportion of CD45+EpCAM+ cells in PBMCs of patients with lung cancer was found to be significantly higher than that of healthy volunteers. Tumor-related serum markers level was also measured in the peripheral blood of these patients using an electrochemiluminescence assay. The correlation between CD45+EpCAM+ cells, carcinoembryonic antigen (CEA), and lung cancer was investigated using receiver operating characteristic (ROC) curve analysis, which showed the sensitivity and specificity of the CD45+EpCAM+ cell to be 81.58% and 88.89%, respectively. Further analysis yielded an area under the ROC curve (ROC/area under the curve [AUC]) of 0.845 in patients PBMCs with lung cancer, which was slightly higher than that of CEA (0.732). Therefore, the detection of CD45+EpCAM+ cells in PBMCs may be helpful for the early screening and auxiliary diagnosis of lung cancer.